Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai Di Unit Pelaksana Teknis (UPT) Dinas Pertanian Wilayah II Kabupaten Gresik - Kusumaningrum, Dini; Sari, Wulan Anjar (GEMA EKONOMI, 2019)
Every organization wanted the employees who work well, and carry out the responsibilities given by the leadership or superiors. Achievement of performance that is still not optimal due to lack of motivation from superiors and work discipline is lacking. To create employee performance to run effectively, in this case employees at UPT Agricultural Department Region II requires motivation accompanied by high work discipline. The purpose of this study is to determine the influence of motivation and work discipline toward employee performance. The research was conducted at UPT Agriculture Department Region II District of Gresik. This research using quantitative approach. The technique of sampling in this research used saturated sampling or total sampling with a total sample of 33 respondents. Techniques of collecting the data using questioner. The research findings from 33 participants using programme SPSS 15.00 version of windows. Based on the result test of t (partial), motivation variable (X1) can't influence toward performance employee (Y). Work discipline's variable (X2) gave significant influence on performance employee (Y). Based on test of F (simultan) showed motivation and work discipline give significant influence on performance employee. Keywords: Motivation, Work Disipline, and Employee PerformanceDOI :10.5281/zenodo.3474607